Evaluating Health challenges Encountered by Internally Displaced Persons (IDPs) in Makurdi L.G.A Government of Benue State, Nigeria - Okutepa, Eleojo Toyin; Bassey, Immaculata Etim (Direct Research Journal of Public Health and Environmental Technology, 2024)
The main objective of this research is to assess the health challenges faced by internally displaced persons (IDPs) in Makurdi. Four corresponding questionnaires and hypotheses were used within a descriptive cross-sectional study design. The study population includes all IDPs currently residing in selected camps in Makurdi Local Government Area, totalling approximately 14,041 individuals in 41,150 households, with a sample size of 437 individuals. The Social Determinants of Health (SDH) theory and the Health Belief Model (HBM) were applied. Descriptive data were expressed as percentages, frequency counts, and mean ± standard deviation, and presented in words and frequency distribution tables. The analysis reveals that IDPs in Makurdi face severe health challenges, including common issues such as diarrhea, pneumonia, malaria, typhoid, and skin infections. Older IDPs report higher incidences of these conditions, while younger IDPs (under 18 years) suffer more from malnutrition. Gender differences show females experiencing more pneumonia and arthritis, while males have slightly higher rates of diarrhea. Healthcare services are generally inadequate, with low satisfaction and poor quality noted overall. Although response times are reasonable, the overall availability and quality of healthcare remain poor. Significant differences in healthcare perceptions are observed based on age and gender, with females rating the importance of healthcare strategies higher than males. The inadequacies in healthcare delivery highlight a critical gap affecting the well-being of IDPs, and consistent patterns across demographics indicate a need for comprehensive and inclusive healthcare intervention.
Keywords: Health challenges; internally displaced persons (IDPs); Makurdi; Social Determinants of Health (SDH) theory; Health Belief Model (HBM)